Effect of plant density on tomato yield inside a plastic greenhouse - Streck, Nereu Augusto; Buriol, Galileo Adeli; Schneider, Flavio Miguel (Pesquisa Agropecuaria Brasileira, 1996)
Yield response of 'Monte Carlo' tomato (an indeterminated growth variety) to plant density inside a plastic greenhouse was evaluated at Santa Maria, Rio Grande do Sul State, Brazil. Treatments were: 20,000, 30,000, 40,000, and 50,000 plants/ha. Tomato plants; were conducted by one steam and spaced 1.0 in between rows. The experiment was carried out in two crop-seasons: winter-spring and autumn-winter. Plants were sown on 7/5/91 and 2/17/92, respectively. In winter-spring season the early fruit yield and the total marketable fruit amount were raised by plant density increase. In autumn-winter season the early fruit yield was raised by plant density increase but the total marketable fruit amount was not affected by plant density. The higher early fruit yield, the fruit yield accumulated until the 5th cluster, and the total marketable fruit amount were obtained in plant densities near to 40,000 plants/ha.